A historical review of fertilizer policies in Nigeria - Balana, Bedru; Fasoranti, Adetunji (International Food Policy Research Institute, 2022)
In its endeavor to improve agricultural productivity, food security, and livelihoods, Nigeria has pursued several approaches in fertilizer policy. Most of these approaches revolved around variants of government-financed subsidy programs. This paper assesses the history of fertilizer policies in Nigeria and the tenets of the fertilizer policies in two recent national agricultural policy documents – the Agricultural Transformation Agenda (ATA) (2010/11-2016) and the Agricultural Promotion Policy (APP) (2016-2020). Our review results show that despite some recent achievements in ATA and APP, Nigerian fertilizer policies have lacked consistency and continuity, which in turn affected the functioning of supply chains, logistics channels including distribution costs, fertilizer prices, farmers’ access to the input, and, ultimately, application rates and crop productivity. Thus, though Nigeria is one of the leading producers of fertilizer in sub-Saharan Africa, fertilizer consumption and farm application rates are generally low (below 20 percent of the application rate per hectare (ha) in developed countries). Moreover, several exogenous factors including poor infrastructure (especially bad roads), credit constraints, extension services, high fertilizer prices, lack of access to information, security threats, and lack of quality control or assurance also affect the functioning of fertilizer supply chains in Nigeria. The newly adopted national agricultural policy (National Agricultural Technology and Innovation Policy (NATIP) promises to build on ATA and APP and gradually deregulate the fertilizer sector to incentivize private sector investments in local fertilizer production and distribution. NATIP also requires the incorporation of practical approaches to tackle important exogenous constraints. We anticipate NATIP’s commitment to policy continuity and addressing exogenous challenges will bring efficiency and effectiveness to the fertilizer sector in Nigeria.